Social Work at Hamad Medical Corporation: Historical Perspective - Nada Eltaiba; Suad Al Hamad (Social Work and Society, 2024)
Understanding the historical context of social work is critical for providing insights into aspects that influenced the profession. The knowledge obtained will give valuable lessons in navigating the complex systems within which social workers practice. Despite the growing interest among researchers in recording the history of social work, there is still a gap in many societies and agencies.  In this paper, we present a brief introduction concerning social service in the Hamad Medical Corporation (HMC), one of the leading institutions in Qatar. To explore historical social work issues, we spoke with a group of pioneering social workers in the field of social work", who have witnessed and even contributed to the beginnings of the development of social work. The participants talked about establishing social work in HMC and some of the narratives relevant to health, mental health, and cultural contexts.